Executive function ratings in educational settings: concurrent relations with cognitive and affective theory of mind. Issue 13 (3rd October 2022) - Longobardi, Emiddia; Spataro, Pietro; Morelli, Mara; Laghi, Fiorenzo
ABSTRACT: The present study examined the way in which behavioural difficulties in cool and hot EFs relate to measures of cognitive and affective ToM in preschoolers. A total of 144 children between 35 and 71 months were assessed with a first-order false-belief task (measuring cognitive ToM), the Test of Emotion Comprehension (measuring affective ToM) and a control task measuring productive language. Teachers filled in the preschool version of the Behavior Rating Inventory of Executive Function (BRIEF-P), a questionnaire examining children's difficulties in educational settings in five different areas tapping both cool (Working Memory, Shift, Plan/Organize) and hot EFs (Inhibition and Emotional Control). Multiple regressions showed that cognitive ToM was predicted by productive language and executive difficulties in the Working Memory subscales of the BRIEF-P, whereas affective ToM was only predicted by age and productive language. Similarities and differences with the results of previous studies are discussed.